2010
DOI: 10.1038/nphys1847
|View full text |Cite
|
Sign up to set email alerts
|

Observation of high-order harmonic generation in a bulk crystal

Abstract: Harmonic generation is a general feature of driven nonlinear systems. In particular high-order harmonic generation (HHG) in atomic gases 1 is the basis for producing attosecond pulses 2,3 . In molecules and clusters, the existence of multiple ionization and recombination sites makes for richer dynamics allowing imaging of molecular orbitals 4,5 , higher conversion efficiency 6 and the possibility of extending the high-energy cutoff 7 . In the strong-field limit, HHG in bulk crystals is fundamentally different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

66
1,222
3
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 1,555 publications
(1,299 citation statements)
references
References 28 publications
66
1,222
3
8
Order By: Relevance
“…We find that harmonic e ciency is enhanced (diminished) for semi-classical electron trajectories that connect (avoid) neighbouring atomic sites in the crystal. These results indicate the possibility of using materials' own electrons for retrieving the interatomic potential and thus the valence electron density, and perhaps even wavefunctions, in an all-optical setting.High-harmonic generation (HHG) in bulk crystal is attributed to the sub-cycle electronic motion driven by an intense laser field [2][3][4][5][6][7][8][9][10][11] . There has been a growing interest in utilizing HHG to probe the electronic structure of solids 8,9,11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We find that harmonic e ciency is enhanced (diminished) for semi-classical electron trajectories that connect (avoid) neighbouring atomic sites in the crystal. These results indicate the possibility of using materials' own electrons for retrieving the interatomic potential and thus the valence electron density, and perhaps even wavefunctions, in an all-optical setting.High-harmonic generation (HHG) in bulk crystal is attributed to the sub-cycle electronic motion driven by an intense laser field [2][3][4][5][6][7][8][9][10][11] . There has been a growing interest in utilizing HHG to probe the electronic structure of solids 8,9,11 .…”
mentioning
confidence: 99%
“…High-harmonic generation (HHG) in bulk crystal is attributed to the sub-cycle electronic motion driven by an intense laser field [2][3][4][5][6][7][8][9][10][11] . There has been a growing interest in utilizing HHG to probe the electronic structure of solids 8,9,11 .…”
mentioning
confidence: 99%
“…Since its first observation by Ghimire et al [1], the physics underlying high-harmonic generation (HHG) in solids has extensively been investigated (for a comprehensive review, see [2]). Recent studies have, for example, demonstrated isolated attosecond XUV pulses emitted from thin SiO 2 films [3], HHG from amorphous fused silica [4], graphene (enhanced by driving ellipticity) [5], or 2D transition metal dichalcogenides [5,6].…”
mentioning
confidence: 99%
“…High-harmonic emission in solids has been a vibrant area of research since it was shown that the excitation of crystals by a strong, longwavelength electromagnetic field generates radiation at high-harmonic frequencies of the driving field's fundamental frequency 5,6 . The strong-field physics of individual atoms in the gas phase is well understood, but the different scaling of the maximum harmonic frequency with the strength of the incident field in solids had hinted at different underlying processes 5 .…”
mentioning
confidence: 99%
“…The strong-field physics of individual atoms in the gas phase is well understood, but the different scaling of the maximum harmonic frequency with the strength of the incident field in solids had hinted at different underlying processes 5 . However, a recent comparative study 7 found that some aspects of the gas-physics picture apply to solids too, such as the importance of controlling the electrons' pathways so as to generate high-harmonic radiation.…”
mentioning
confidence: 99%